Mobile credit scoring and recording - Maisiba, Jack Maumba (Strathmore University, 2021)
Credit Scoring has in recent years become a very important issue especially with the growth of the money lending sector. The harsh economic times have dictated the need for more lending due to the very static disposable income people have against the ever-changing economic factors. Interest rates charged by banks and digital lenders are pretty high which has led more and more people from considering the sector when it comes to lending but they look to family and friends. Companies are also finding themselves in trouble with lenders with access to credit scores. A newly developed credit scoring system is in place to better the lives of individuals and set out to incorporate more categories into calculating the ratings. A research method of different online and mobile applications was used to access the information gathered to calculate credit ratings. The introduction of a mobile credit score application with accurate information based on European and American bank information and credit categories will allow users to effectively find out information required for acquiring loans and any other finances. Methodology to be used in creating the system was prototyping as it will be possible to carry out initial tests and ensure at early stages all functional requirements are met. The prototypes will also allow for feedback to changes to be made in the system to improve the quality of life. This study is set to form a large step towards debt management in the country and credit score literacy
An Information system project 2 Proposal submitted to the School Of Computing and Engineering Science In Partial Fulfillment Of The requirements for the award of the Bachelor’s Degree in Business Information Technology of Strathmore University
Keywords: Mobile credit; Recording; Credit scoring